Hallyuwood: Korea's Comparative Advantage in the Global Motion Picture Industry - Miroudot, Sébastien (Archīum Ateneo, 2024)
After Hollywood and Bollywood, the recent success of the Korean motion picture industry has been described as the rise of “Hallyuwood,” suggesting that Korea has become the third pillar of the global motion picture industry. In order to explain the emergence of Hallyuwood, this paper uses a global value chain (GVC) approach and highlights some of the economic determinants in the internationalization of the Korean movie industry. Using input-output data and firm-level information, the paper first analyzes the position of Korea in the motion picture GVC and assesses the ways in which the movie production has become more global. The results indicate that Korea is the country with the strongest comparative advantage in the motion picture value chain. The paper then discusses different aspects of the internationalization of the Korean motion picture industry, in particular: the role of co-production and foreign partners, the concentration and vertical integration of the industry, and the creation of a global brand. Finally, the paper looks at the main challenges the Korean industry will face if it desires to further expand and remain competitive, discussing government policies and the impact of the rise of China on Korea’s movie industry. Overall, the paper emphasizes that while typically national, cultural products can also benefit from global business strategies.